Evaluation of Different Collections of Hypericum perforatum L. in Himachal Pradesh for Biomass Yield and Hypericin Content - Singh, Joginder; Rajasekaran, A.; Raina, R.; Rana, R. (Indian Forester, 2011)
The present study evaluated different collections of Hypericum perforatum L. growing in Himachal Pradesh for biomass yield and hypericin content. The maximum fresh weight (49.98 g/plant) and dry weight (16.04 g/plant) was recorded in Hyp-V collected from Dochidhar area of Shimla District while Hyp-Vl collected from Koftdhar had maximum height (59.46 em). The maximum hypericin (0.109 percent) was recorded in Hyp-II and Hyp-VlI collections.